Decline in neutralising antibody responses, but sustained T‐cell immunity, in COVID‐19 patients at 7 months post‐infection. Issue 7 (26th July 2021) - Chen, Jun; Liu, Xiaomin; Zhang, Xinyu; Lin, Yixiao; Liu, Danping; Xun, Jingna; Wang, Zhenyan; Gu, Ling; Li, Qian; Yin, Dan; Yang, Junyang; Lu, Hongzhou
Abstract: Objectives: This study aimed to explore the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐specific humoral responses and T‐cell responses in patients who have recovered from coronavirus disease 2019 (COVID‐19) to understand the natural protective immune responses and to facilitate the development of vaccines. Methods: We conducted a combined assessment of the changes in neutralising antibody levels and SARS‐CoV‐2‐specific T‐cell responses over time in 27 patients up to 7 months after infection. Results: The neutralising antibody remained detectable in 96.3% of the patients at their second visit at about 7 months post‐onset of symptoms. However, their humoral responses, including titres of the spike receptor‐binding domain IgG and neutralising antibody, decreased significantly compared with those at first clinic visit. By contrast, the proportions of spike‐specific CD4 + T cells, but not CD8 + T cells, in COVID‐19 patients after recovery were persistently higher than those in healthy controls. No significant change was observed in the proportion of spike‐specific CD4 + T cells in patients who had recovered from COVID‐19 within 7 months. Conclusion: The SARS‐CoV‐2‐specific T‐cell immune responses persisted, while the neutralising antibodies decayed. Further studies are needed to extend the longevity of neutralising antibodies and to evaluate whether these T cells are sufficient to protect patients from reinfection. Abstract : We followed up COVID‐19 patients discharged from the hospital up to 7 months post infection. We found that the neutralizing antibody responses are declining while T‐cell immunities are sustained in COVID‐19 patients during the follow‐up.